INFLUENCE OF TRADITIONAL DANCE TRAINING PROGRAMS ON DYNAMIC BALANCE OF PEOPLE WITH INTELLECTUAL DISABILITY: A SHORT REVIEW - Vasileios, K. Tsimaras (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Traditional dance is gaining popularity as an intervention choice for improving poor balance ability of people with intellectual disability (ID). Balance improvement for individuals with ID through dance provides opportunities for participation in sport activities and promotes independent living. This short review provides in brief research evidence of dynamic balance improvement as measured by means of a balance deck in duration of 30, 45, and 60 sec intervals, highlighting the need to incorporate traditional dance programs in Physical Education (PE) lessons applied on participants with ID. Overall, traditional dances provide emotional and cognitive interaction that has a direct positive effect on quality of life and successful motor performance of individuals with ID.